Customer perception of service quality in public transport - Grujičić, Dragana; Ivanović, Ivan; Jović, Jadranka; Đorić, Vladimir (Transport, 2014)
This paper presents the research and analysis process showing that transport system customers have a specific perception of service quality, as an indicator of transport system. Determining satisfactory level of service quality implies knowledge of travel demand and travel behaviour. There are a lot of elements that define the transport system quality. The goal of this paper is to identify the public transport system’s service quality elements that should be primarily acted on, in order to increase the level of service quality from transport system users’ (public transport users’ and non-users’) point of view, with minimal investment. The paper describes a specifically defined research methodology for determining service quality elements that should be primarily acted on, from the transport system users’ point of view. Methodology involves the use of Importance Performance Analysis (IPA) which is upgraded with the state preferences analysis. Presented methodology, which is used to determine user perception of service quality, can be considered to be universal. This methodology can be applied in other cities, with additional research that must precede its use. The methodology was tested on transport system users in Belgrade. First Published Online: 22 Sep 2014